Ode 30 By Horace in the English Poetic Tradition: Towards the Problem of Multiple Creative Interpretation (Proceedings of Southern Federal University. Philology, 2017)
Svetlana V. Nikolaeva (Rostov-on-Don, Russian Federation)Multiple creative interpretation is considered as a tool of a verse text cross-cultural transition and adaptation. Ode 30 by Horace is chosen as an object of interpretation (prototext). the distinctive features of English poems generated as a result of the prototext decoding and hence containing references to the original poem are analyzed. The character of outer reference, as well as range of its functions, are specifically pointed out.Key Words: interpretation, linguistic hermeneutics, verse text, prototext, translation, corporate language personality.DOI 10.23683/1995-0640-2017-3-103-112